Models of distribution logistics of technical defense products under wartime risk conditions - Polupan, Yuriy; Malyeyeva, Olga (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2025)
The subject of this article is the processes of organization and optimization of the distribution logistics of technical defense products under wartime conditions, in particular, the development of a network logistics structure considering reverse flows, risks, and limited resources. The purpose of the study is to improve the efficiency of distribution logistics of technical defense products in wartime by constructing an adaptive structure of logistics flows and developing a mathematical optimization model that accounts for risks and resource constraints. The article addresses the following tasks: analysis of the specific features of distribution logistics for technical defense products in combat conditions; development of a structural model of logistics flows that considers direct and reverse links as well as the reuse of components; construction of a mathematical model for optimizing logistics processes with consideration of time costs, delay risks, and resource constraints; justification of the application of scenario analysis and adaptive planning to enhance the resilience and continuity of supply under uncertainty. The following methods are applied: a systems approach, structural decomposition of logistics processes, risk-based approach, constrained mathematical modeling, scenario analysis, and adaptive planning. The results obtained include the construction of a structural model of logistics flows for supplying the Armed Forces of Ukraine, which takes into account direct and reverse flows as well as component reuse; the development of a mathematical model for optimization of distribution logistics with an objective function of minimizing time and constraints on supply volume, total risk, and the number of routes. It is demonstrated that risk consideration significantly affects the choice of optimal routes and strategies. The feasibility of using scenario analysis and adaptive planning to ensure continuity of supply in combat conditions is substantiated. Conclusions. The proposed structural and mathematical models make it possible to reduce the logistics cycle time, increase the resilience of the logistics system to risks, and ensure rapid response to changing circumstances. The use of reverse logistics and component reuse helps reduce costs and mitigate resource shortages. Scenario analysis and adaptive planning are effective tools for managing the distribution logistics of technical products under uncertainty and wartime risks.